Sleep disorder is associated with increased risk of major adverse cardiovascular events in patients with schizophrenia - Wu, Jinbo; Wang, Tingting; Jiang, Xiaomei (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the association of sleep disorder with the risk of major adverse cardiovascular events (MACEs) among patients with schizophrenia—a population known to have heightened cardiometabolic vulnerability, yet underexplored in terms of sleep-related cardiovascular risk.MethodsThe cross-sectional study included 1,072 participants diagnosed with schizophrenia between January and December 2022. The sleep disorder was defined based on self-reported sleep duration, insomnia, and daytime sleepiness, and collected via self-completed questionnaire. Patients’ MACEs including fatal and non-fatal myocardial infarction (MI), fatal and non-fatal stroke, and cardiovascular death were collected from chart review. Multivariate logistic regression model was employed to assess the association of sleep disorders with the risk of MACE after controlling for potential confounding factors.ResultsSleep disorders were common, with 25.7% reporting insomnia, 30.0% reporting short sleep duration (<6 h), and 36.0% experiencing excessive daytime sleepiness. Among the 1,072 patients with schizophrenia, 20.3% experienced a MACE. Participants who have insomnia, short duration of sleep or excessive daytime sleepiness were more likely to have MACEs compared with those without these sleep disorders (all p < 0.01). Multivariate logistic regression indicated that insomnia (OR = 1.88, 95% CI: 1.26–2.78; p < 0.01), short sleep duration (OR = 1.66, 95% CI: 1.17–2. 35; p < 0.01), and excessive daytime sleepiness (OR = 1.55, 95% CI: 1.13–2.12; p < 0.01) were significantly associated with the risk of MACE after controlling for potential confounding factors.ConclusionSleep disorders are significantly associated with a higher risk of MACEs in patients with schizophrenia.